Heaven on earth a journey through sharia law - Kadri, Sadakat (London Bodley Head, 2011)
Almost 1400 years after the Prophet Muhammad first articulated God's law - the sharia - its earthly interpreters are still arguing over what it means. Hardliners reduce it to amputations, veiling, holy war and stonings. Others say that it is humanity's only guarantee of a just society.
Laying down the law -- From revelations to revolution -- The formation of the law schools -- Commanding the faithful -- The Sunni challenge and the Shi°a response -- The caliphate destroyed: a shadowless God -- The reinvention of tradition: salafism -- Jihad: a law-torn world -- Innovation and its discontents: Islamic law and the challenge of change -- Punishment and pity: the modern revival of Islamic criminal law -- "No compulsion in religion'? Apostasy, blasphemy and tolerance -- Heaven on earth.
Includes bibliography ([p.299]-316) and index.
Keywords: Islamic law -- Popular works; Natural law -- Religious aspects